Europa po Traktacie z Lizbony – słowa i rzeczywistość - KONOPACKI, Stanisław (Przegląd Politologiczny, 2018)
The Treaty of Lisbon, which became effective on December 1 2009, provides for the transformation of the European Union into a more democratic, efficient and united community. This paper attempts to assess to what extent its provisions are reflected in the current reality of a united Europe. On the one hand, democratic legitimization of the EU is growing as a result of increasing competencies of the European Parliament, the rights of national parliaments, and so-called citizens’ initiatives. However, the turnout in the last European elections, the increasing popularity of extremist right-wing parties, the work of the European Convention and restrictions imposed on the free movement of persons show that EU practice is far from the complete implementation of democratic values. Secondly, the Lisbon Treaty provides for higher EU efficiency in the international arena. This cannot be achieved, though, by electing people devoid of charisma, experience and a vision of a united Europe to the highest positions, such as EU president or chief of diplomacy. Last but not least, the new treaty provides for energy solidarity. Yet the work of the European Parliament, which is expected to translate these words into practice, is burdened by an increasing number of doubts and difficulties.